The Phone Shop : growth and the entrepreneur. (Part A) - Mitchell, Claire; Beswick, Claire; Zidel, David ([London] : SAGE, 2016)
In August 2006, the lease on The Phone Shop - a business that the Brill family had run for the past 18 years - was up for renewal. In recent years, the shop had not performed well, but Eran Brill believed that because it had developed a strong brand over the years, there was potential to make it profitable once again. Still, a lot of people felt it was best simply to close the shop down. Brill wondered whether he should listen to this advice or to his own instincts, and if the latter, what he could do to turn the shop around.
Originally Published in: Mitchell, C., Beswick, C., & Zidel, D. (2009). The Phone Shop: Growth and the Entrepreneur (Part A) WBS-2009-17a. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Phone Shop (Firm); Small business -- Finance -- Case studies; Family-owned business enterprises -- Case studies